PARA MALAIKAT : Tinjauan Teologis â€“ Kultural atas Peran Malaikat - Sabato, Salvatore (LOGOS, 2005)
In the religious life of the Middle East and in the Christian Bible, the role of angels is very broad and important. The angels are prominent religious figures one cannot just neglect. To understand their presence, every religion, included monotheistic religions, expresses it in cults, literatures and arts in forms of painting, sculptures, music, etc. The Angels are considered as â€œghostsâ€ who abide in one layer (stratum) of skies located in the middle and become medium between â€œthe invisibleâ€ (God) and â€œthe visibleâ€ (Human Being). The significance and the main function of the angels are as â€˜Mesengerâ€™ to reveal or to interpret the wishes of those who delegate them and also to protect human being. Finally, the angels become raw material of â€œcultivationâ€ by the human being itself, without loosing their functions and roles.